2018
DOI: 10.1002/adtp.201800023
|View full text |Cite
|
Sign up to set email alerts
|

Bi‐Enzymatic Embolization Beads for Two‐Armed Enzyme‐Prodrug Therapy

Abstract: Embolic beads, a successful tool for localized, site-specific drug delivery, are engineered herein to contain the toolbox of enzyme-prodrug therapy (EPT). EPT offers facile means to synthesize diverse drugs at their nominated concentrations; individually, in sequence, or in a combination. The authors investigate alginate beads as embolic bodies and screen alginate type and bead production parameters as factors to control activity of the immobilized enzymes. Engineered embolic bodies are armed with bi-enzymatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 44 publications
(52 reference statements)
0
8
0
Order By: Relevance
“…The rationale for the focus on microgels is related to the large interest in exploiting polyelectrolyte hydrogel materials in the form of microgels both to address fundamental issues and in numerous applications. Furthermore, the microgel mechanical properties may differ from that of the bulk specimens of the same constituents either due to statistical variation of mechanical properties of microgels due to structural heterogeneity [ 1 ], combination of materials to yield multicomponent microgels different from that possible in bulk [ 2 ], coating of the microgels with the possible consequence of the mechanically stratified structure and immobilization of components in the microgels [ 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The rationale for the focus on microgels is related to the large interest in exploiting polyelectrolyte hydrogel materials in the form of microgels both to address fundamental issues and in numerous applications. Furthermore, the microgel mechanical properties may differ from that of the bulk specimens of the same constituents either due to statistical variation of mechanical properties of microgels due to structural heterogeneity [ 1 ], combination of materials to yield multicomponent microgels different from that possible in bulk [ 2 ], coating of the microgels with the possible consequence of the mechanically stratified structure and immobilization of components in the microgels [ 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to systemic administration, local administration using biomaterials is a promising approach to ensure enzymes and drugs are retained at the desired location in the body. A few pioneering studies regarding focal administration approaches in EPT have been reported. Zelikin and colleagues have reported excellent examples of focal administration EPT systems using electrospun fibers and hydrogel beads as biomaterials. , These studies successfully demonstrated the potential utilities of focal administration approaches in EPT. In order to advance this field, further investigation using other biomaterials is necessary.…”
Section: Introductionmentioning
confidence: 99%
“…Zelikin and colleagues have reported excellent examples of focal administration EPT systems using electrospun fibers and hydrogel beads as biomaterials. 25,26 These studies successfully demonstrated the potential utilities of focal administration approaches in EPT. In order to advance this field, further investigation using other biomaterials is necessary.…”
Section: Introductionmentioning
confidence: 99%
“…In our own past work, we predominantly relied on β-galactosidase as the enzyme and the corresponding commercially available β-gal-NONOate as the prodrug. Enzymes were successfully embedded into hydrogel embolic bodies, [46] liposomes, [35] electrospun fibers, [47] and on the surface of 316L metallic wires. [36] NO generated using these biomaterials were able to elicit physiologically relevant effects such as to induce vasodilation [36] and reduce intraocular pressure [35] in ex vivo animal models.…”
Section: Introductionmentioning
confidence: 99%